The Role of Mathematics in Big Data Analysis - Jagadeesh R., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The exponential growth of data in recent years has made Big Data analysis a central tool across various industries, from healthcare to finance and social networks. While computational tools and software frameworks often receive the most attention, mathematics forms the foundational core enabling effective data analysis. This article explores the pivotal role of mathematics in Big Data analysis, focusing on the essential mathematical disciplines-linear algebra, calculus, probability and statistics, discrete mathematics, and optimization-that underpin data processing, modeling, and interpretation. The discussion includes applications, challenges, and future directions, highlighting the importance of mathematical rigor for accurate, scalable, and ethical Big Data analytics.
Keywords: Big Data; Mathematics; Linear Algebra; Probability; Statistics; Optimization; Machine Learning